Debt for status? Consumer credit, ordinary consumption, and the sense of place - Felipe González López (Finance and Society, 2023)
The quest for social status is usually considered one of the main drivers of the demand for consumer credit. This article provides a nuanced take on consumer credit by exploring the interaction between consumption, borrowing, and class identity. To do so I pursue a cultural class analysis inspired by the work of Pierre Bourdieu. Drawing from 26 semi-structured interviews, the article has two main findings. First, it shows that people engage in borrowing not only to gain prestige, but also to assert their belongingness to symbolic groups, which embody the values of imagined communities. Second, against the idea that borrowing is undertaken mainly for conspicuous consumption, the article's findings show that middle- income families in Chile borrow to consume 'ordinary' goods. Through the consumption of these goods, the Chilean middle classes seek to stabilize their class identities through their life trajectories, thereby achieving a sense of place in a changing environment. These findings lead me to focus on the normalization of credit and the process through which borrowing practices turn consumer goods from wants into needs, ratcheting up the demand for credit. The article argues that this is an overlooked way in which competitive dynamics drive the demand for credit, which is a missing link in the explanation for the rise of household debt.
Keywords: 300; Consumer credit; consumption; cultural class analysis; household debt; Pierre Bourdieu